2016
DOI: 10.1097/pgp.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Serous Tubal Intraepithelial Carcinoma and Non-Neoplastic Conditions of the Fallopian Tubes in Grossly Normal Adnexa: A Clinicopathologic Study of 388 Completely Embedded Cases

Abstract: Serous tubal intraepithelial carcinoma (STIC), the putative precursor of the majority of extrauterine high-grade serous carcinomas, has been reported in both high-risk women (those with a germline BRCA mutation, a personal history of breast carcinoma, and/or family history of breast or ovarian carcinoma) and average risk women from the general population. We reviewed grossly normal adnexal specimens from 388 consecutive, unselected women undergoing surgery, including those with germline BRCA mutation (37 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Coexistence of these two tumor types is considered rare, confirmed in this study where STIC was discovered in only 0.2% of endometrioid neoplasms. However, other studies have suggested an association between STIC and endometrioid neoplasia [16,20]. Moreover, we have identified an association, albeit unclear, between benign proliferations with a "clonal" appearance (stem cell outgrowths (SCOUTs)) in the tube -some with endometrioid histology -and HGSC [21,22].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Coexistence of these two tumor types is considered rare, confirmed in this study where STIC was discovered in only 0.2% of endometrioid neoplasms. However, other studies have suggested an association between STIC and endometrioid neoplasia [16,20]. Moreover, we have identified an association, albeit unclear, between benign proliferations with a "clonal" appearance (stem cell outgrowths (SCOUTs)) in the tube -some with endometrioid histology -and HGSC [21,22].…”
Section: Discussionmentioning
confidence: 58%
“…Germane to both goals is the prevalence of STICs in women who are not considered at high risk for HGSC. The prevalence has not been established in large studies but at institutions where complete microscopic examination of the distal fallopian tube has been implemented (SEE-FIM protocol), it is estimated that the frequency of STIC in these women is between 0.6 and 1.1% [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Though STICs are associated chiefly with HGSC, they are not exclusive to HGSCs of the ovary, fallopian tube, and peritoneum. STICs are also found in the fallopian tubes of patients with (high-grade) endometrial serous carcinoma (8–23%) [ 47 , 106 , 143 , 144 ], as well as ones from patients with nonserous endometrial carcinoma or endometrial hyperplasia (1.1%) [ 140 ] ( Table 3 ). STICs are also found in the fallopian tubes of 3% (2/64) of women undergoing surgery not related to ovarian, tubal, or peritoneal malignancy [ 101 ].…”
Section: Origins Of High-grade Serous Ovarian Cancer (Hgsc)mentioning
confidence: 99%
“…Particularly critical, yet unknown, is the clinical significance of STIC in the general population where 85–90% of HGSC cases occur. The information on the prevalence of STICs in the general population is limited, but several studies suggest that it could vary from 0.8–3.1% [ 101 , 140 , 142 ], while the lifetime risk of ovarian cancer is 1.3% (one in 78 women) [ 50 , 162 ]. Like DCIS, most likely, some STICs would possess malignant potential, while more STICs would not.…”
Section: Origins Of High-grade Serous Ovarian Cancer (Hgsc)mentioning
confidence: 99%
“…In the nonprophylactic setting, Morrison et al14 and Gilks et al15 reported respective mean ages of 62.7 and 57 years among patients with STIC. Under non-neoplastic conditions of the FT, the incidence of STIC was also associated with advanced patient age 16. STIC is commonly located in the tubal fimbria and is associated with p53S 17.…”
Section: Discussionmentioning
confidence: 99%